The Relationship Among Economic Structure, Sectoral Workforce, and Community Welfare in Bali Province - Yasa, I Nyoman Mahendra (Jurnal Ekonomi Kuantitatif Terapan; 2021: Vol. 14, No. 2, Agustus 2021 (pp.243-431), 2021)
Economic performance that can be achieved by regions cannot be separated from the influence of sectoral economic policies. The difference in economic performance, particularly the economic growth achieved by each region, affected to the inequality in development, which is reflected in the structure of the regional economy. The purpose of this study is to analyze the effect of changes in the economic structure on the structure of sectoral employment and the welfare of the people in Bali Province. Data were analyzed by path analysis. The results shows that the changes in economic structure have a positive and significant effect on the structure of employment. Partially, the changes in the economic structure and the structure of employment has a negative and significant effect on people's welfare. Changes in the economic structure have an indirect effect on people's welfare through the structure of employment in Bali Province.